Small Intestine Strangulating Obstruction by Mesenteric Pedunculated Lipoma in a Criollo Mare - de Souza, Rafaela Pinto; Rafael, Leandro Américo; Mousquer, Mariana Andrade; Müller, Vitória; Àvila, Plínio Amélio Ocanha; Nogueira, Débora Machado; Curcio, Bruna da Rosa; Wayne Nogueira, Carlos Eduardo (Acta Scientiae Veterinariae, 2020)
Background: The abdominal lipomas are benign tumors of hyperplastic growth that originate from mesenteric adipose tissue, most commonly in the small intestine. Pedunculated lipoma strangulation occurs when the pedicle wraps around an intestinal loop and its mesentery, obstructing the intestinal lumen and blood supply of the affected segment. The aim of the present study is to report a case of a Criollo mare presenting a strangulating obstruction of the jejunum and ileum by a pedunculated lipoma, focusing the discussion in the causes and epidemiology of this alteration. Case: A 24-year-old Criollo mare with a body condition score 8 out of 9 was referred to a Veterinary Clinical Hospital of the Federal University of Pelotas (HCV-UFPel) presenting acute abdominal pain. At the hospital, the mare was presenting mild signs of abdominal discomfort. At the initial clinical exam, the mare had an increased heart and respiratory rates, normal body temperature, hyperemic mucous membranes, capillary refil time of 3 s and absent gut sounds in all four quadrants during auscultation. Mild dehydration was present, increased fibrinogen and serum lactate. Rectal palpation revealed distention of the small intestine by gas, during abdominal ultrassonography the small intestinal wall thickness was found increased. Peritoneal lactate was 11 mmol/L and protein was 6 mg/dL. Due to the clinical findings during the exam, an exploratory celiotomy was performed. Necrosis of the final third of jejunum and the entire extension of ileum was found. Examining the compromised intestinal portion, it was observed a linear structure strangulating two segments of the small intestine. Taking into account the extensive area of irreversible necrosis and the advanced age of the patient, euthanasia was performed. The mare was then referred for necropsy and findings confirmed the strangulation of the final portion of the jejunum and all the extension of the ileum caused by a mesenteric pedunculated lipoma. Discussion: Increased mesenteric fat can predispose horses to the development of mesenteric lipomas. Although there is no scientific evidence of the association of mesenteric lipoma and obesity, it has been observed that pedunculated lipomas are more common in horses with metabolic alterations, for example, Criollo breed, that is potentially predisposed to develop metabolic disturbances. Elderly horses are at the highest risk of colic by mesenteric lipoma, as well as geldings, however, others authors describe that females are more commonly affected. Horses considered of short stature are more predisposed when compared to jumping or race horses. Pedunculated lipoma occurs in 18% of all cases of treated colic and is found more frequently in the small intestine when compared to the smaller colon. In most cases, surgery is indicated and resection of the pedicle and the affected segment may be necessary, however, in this case, the extensive area of intestinal necrosis and the impossibility of externalization of the affected segment lead the decision to proceed with euthanasia. In conclusion, the mare of the present study had an advanced age and a high body condition score, which the authors’ believe were two predisposing factors that increased the risk of it developing a mesenteric lipoma. Considering that, further epidemiologic studies should be conducted to better understand this relation.